The fracture of exile. Review of the work Que Dios protege a los malos (1979) (God Protects the Wicked) by Myriam Bustos Arratia - Rojas Mejías, Diana (2026)
This article presents a comment of the literary work Que Dios protege a los malos (1979) written by Myriam Bustos Arratia, a Chilean writer exiled in Costa Rica since 1974. This text contains twelve stories located in Costa Rica and Chile during 1973-1976, which refer to events such as the tensions prior to the coup d’état, the social demonstrations, the alliances between parties, the takeover of buildings, the uncertainty of the disappeared people and the exile, from the daily life of the characters with different social origins and militances. The review proposes, if we understand the literary work as a text in and about exile, we can find three themes: the criticism of the government of Salvador Allende, the existence of social classes as one of the causes of tension and the appearance of emotional states associated with the coup. It is concluded that the text shows the fractures of the coup and exile in the subjects, reflected in the separation of families, the search for refuge, the expectations of return, the fear, the loneliness, and the hopelessness.